Uso de técnicas espectroanalíticas na avaliação de amostras de placas de circuito impresso de lixo eletrônico - Santos, Jozemir Miranda dos (Universidade Federal de São Carlos, 2015)
The increase in the consumer electronics equipment, especially, the cell has aroused the academia and society in general interest. Such equipment when obsolete became part of the so-called junk mail. Among the components of this type of waste, are the printed circuit boards (PCB’s). The concentration of toxic elements such as Cd, Cr and Pb these PCB has proved high. Because of this situation becomes important to develop analytical methodologies for evaluation of these dangerous elements in PCB. Among the analytical techniques available, the most used in the determination of these elements has been the ICP OES. The evaluation of samples PCB by ICP OES performed in this study revealed that in addition to the regulated elements by RoHS (Cd, Cr and Pb), are present in high quantities, the elements Ba (2% w/w) and As (400 mg/kg). The Cu element was the one with the highest levels of concentration in some samples amounted to 35% (m/m). The use of a multivariate analysis such as PCA, showed some correlation between certain elements of the PCB. This is observed for the elements Ba and Ni, and also to the As, Cr and Fe. Alternatively to the use of techniques that require a pretreatment of the samples comes LIBS. The obtained emission spectra provided important information about the composition of these PCB’s. An analysis of the spectra reveals the presence of emission lines of elements such as Ba, Cd, Pb, Ni, Cu, Fe, Sb, among others. The elements that provide the most intense emission lines were Cu and Ba. Based on the obtained reference concentration by ICP OES and the values of the area and intensity of the spectra obtained, the construction of multivariate calibration models has been proposed. Employing MLR was possible to build the multivariate calibration models for elements of interest. However, due to lack of verified correction, among the area parameters, maximum intensity and reference concentrations, the proposed models are considered viable. However, the use of LIBS for characterization purposes samples for the presence of an element, shown to be feasible from a qualitative point of view.
Techniques espectroanalíticas use the boards samples assessment of printed circuit electronic waste
Keywords: Lixo eletrônico; Espectroanalítica; LIBS; Quimiometria; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA